A CASE STUDY OF STUDENTS' CREATIVITY IN SOLVING MATHEMATICAL PROBLEMS THROUGH PROBLEM BASED LEARNING - Farrah Maulidia; Rahmah Johar; Andariah Andariah (IKIP Siliwangi and I-MES, 2019)
Creativity could be interpreted as a person's cognitive abilities in solving problems by bringing up new ideas. The problems of students’ math achievement lows is math presented as finished product, ready to use, abstract and taught mechanistic. This case can be lead to the creativity of the less developed students because students are not given the opportunity to think and use theirs ideas in solving mathematical problems. Problem Based Learning Model is a learning model that emphasizes the concept and information outlined from the academic discipline. The purpose of this study is to analyzed students’ creativity in solving mathematical problems through Problem Based Learning model (PBL) in class VIII-1 MTsN Model Banda Aceh. Data qained based on the students’ worksheet in groups. The data acquisition is categorized into 5 levels (highest level 4 and lowest level 0) which is analyzed descriptively. The results is three groups were at level 4 with very creative categories, one group is at level 3 with creative category and another group is at level 2 with deeply creative enough category. To the conclusion is PBL model could cultivate the students’ creativity in solving mathematical problems.